Qur’anic Foundations of Strategic HRM: Applying Makki and Madani Verses in Islamic Educational Institutions - Jamaludin, Muhamad; Rahmadi Bagus Wijaya (Journal of Islamic Education Management Research, 2024)
Purpose – This study aims to integrate Islamic spiritual values into strategic Human Resource Management (HRM) practices within Islamic educational institutions by contextualizing Makki and Madani Qur’anic verses. It introduces a dual-framework model that enhances managerial effectiveness through spiritual grounding and normative regulation. Design/methods – Utilizing a qualitative literature-based methodology, this research applies content and thematic analysis to both Qur’anic texts and institutional HRM policies. Makki verses, which emphasize moral development and spirituality, are interpreted as foundations for character-building, while Madani verses, with their legalistic and regulatory content, guide institutional governance. Data triangulation, expert validation, and inter-coder reliability checks are employed to ensure analytical rigor. Findings – The study reveals that HRM strategies grounded in the Makki-Madani framework support a balanced approach to managing personnel by fostering ethical conduct (Makki) and enforcing structured policies (Madani). Institutions adopting this approach demonstrate higher adaptability to external changes and stronger internal cohesion. However, the lack of empirical data remains a limitation, suggesting the need for further field-based validation. Research implications/limitations – While this model offers theoretical advancement in integrating Islamic principles into HRM, its reliance on qualitative sources and the absence of quantitative evidence limit the generalizability of the findings. Future studies should include case studies, performance metrics, and stakeholder interviews for broader validation. Practical implications – Educational institutions can apply the Makki-Madani framework to improve staff development, policy formation, and organizational resilience. This duality fosters a sustainable work culture rooted in spiritual ethics and adaptive governance, enabling effective responses to regulatory and moral challenges. Originality/value –This is your opportunity to provide readers with an analysis of the value of your results. It’s a good idea to ask colleagues whether your analysis is balanced and fair, and again, it is important not to exaggerate. You can also conjecture what future research steps could be.